The Correlation between Social Media Usage and Reading Ability of English Department Students at University - Mesa Salsabila Sadha; Novitri Novitri; M. Syarfi (Institut Agama Islam Negeri Palopo, 2022)
This research aims to find out the correlation between social media usage and reading ability of the English department students at University of Riau. The research design was descriptive correlational that focused on the quantitative approach. The population of the research is the third year students of English department with 73 students involved as the research samples. To collect the data, the researcher used two research instruments; a questionnaire and a test. The questionnaire is to gain the data of the students’ social media usage while the test is for the data of the students’ reading ability. The analysis of the data was carried out using IBM SPSS Statistics. The findings revealed that the mean score of the students’ social media usage is 53.29, interpreted as ‘average’, whereas the mean score of the students’ reading ability is 66.75, interpreted as ‘good’. Then this research discovered the correlation coefficient between the two variables is 0.622, and following the classification of correlation by Sugiyono (2014), this number denotes a ‘high’ and ‘positive’ correlation. Also, the determinant coefficient is 0.387, indicating that the students’ social media usage has 38.7% influence on their reading ability, leaving the other 61.3% to other factors, such as the complexity of the text, the environmental conditions, the anxiety during reading comprehension, interest and motivation, etc. Having found these findings, it can be confirmed that social media usage can influence students’ English reading ability very well if they start using it wisely.